2004
DOI: 10.1161/01.hyp.0000111138.78714.1a
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Nitric Oxide Modulates Vascular Action of Aldosterone in Renal Arteriole

Abstract: Abstract-We have recently demonstrated that aldosterone causes nongenomic vasoconstriction by activating phospholipase C (PLC) in the preglomerular afferent arteriole (Af-Art). In the present study, we tested the hypothesis that endothelium modulates this vasoconstrictor action by releasing nitric oxide (NO). In addition, to study the post-PLC mechanism, we examined possible contributions of phosphoinositol hydrolysis products. Rabbit Af-Arts were microperfused at 60 mm Hg in vitro, and increasing doses of ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 42 publications
3
54
1
3
Order By: Relevance
“…18 The endothelium may modulate this vasoconstrictor effect by NO release. 19 Aldosterone induced a dose-dependent vasoconstriction in microperfused rabbit afferent arterioles, which was enhanced by disrupting the endothelium. Inhibition of NO synthase induced a similar effect, which was inhibited by chelerythrine, a protein kinase (PKC) inhibitor.…”
Section: Endotheliummentioning
confidence: 98%
“…18 The endothelium may modulate this vasoconstrictor effect by NO release. 19 Aldosterone induced a dose-dependent vasoconstriction in microperfused rabbit afferent arterioles, which was enhanced by disrupting the endothelium. Inhibition of NO synthase induced a similar effect, which was inhibited by chelerythrine, a protein kinase (PKC) inhibitor.…”
Section: Endotheliummentioning
confidence: 98%
“…Arima et al 64 reported that aldosterone can activate NOS 3 in renal arterioles, leading to NO production; however, the mechanism involved was not investigated. Taylor et al 65 found that in ET B receptor-deficient rats, medullary NOS activity and renal endothelin production are decreased, indicating that renal endothelin regulates NOS 3 activity as reported for the thick ascending limb.…”
Section: Hormonal Regulation Of Nosmentioning
confidence: 99%
“…However, substantial evidence has emerged to show that aldosterone also plays an independent role in mediating cardiovascular damage. It plays a major role in cardiac and vascular remodelling, regulating collagen turnover and fibrous tissue formation, though some evidence suggests that it may have short-term vascular effects, leading to vasoconstriction in both in vitro studies 29 and in vivo in man. 30,31 Long-term increases in aldosterone lead to deleterious effects on the vascular matrix, by increasing collagen content and fibrosis.…”
mentioning
confidence: 99%